Regulasi Jual Beli Oline Dengan Sistem Dropship Dalam Perspektif Hukum Islam - Anjeli; Hidayanti, Sri; Herdiansyah (Jurnal Indragiri Penelitian Multidisiplin, 2025)
The rapid growth of e-commerce in Indonesia, driven by technology, wider internet access, and changing lifestyles, has popularized the dropshipping system. Sellers in this system ship orders directly from suppliers to consumers without holding inventory. This method facilitates starting a business with low capital and risk but also raises legal issues like consumer protection, potential fraud, and business disputes. Given Indonesia's predominantly Muslim population, Islamic legal aspects of online transactions are crucial. Sharia principles such as transparency, honesty, and fairness must be applied to ensure transactions are legally valid and align with Islamic values. This research analyzes legal regulations for online sales using dropshipping in Indonesia and their application from an Islamic law perspective. It aims to provide a deep understanding of the rights and obligations of parties in the dropshipping system and offer regulatory improvement recommendations to support the healthy and sustainable growth of e-commerce in Indonesia.